Re-Framing the Interlinked between Demographic Transition and Land-Use Change in Developing Countries Peri-urbanization - Christiawan, Putu Indra; Nguyen, Thi Phuoc Lai (Indonesian Journal of Geography, 2024)
Recent peri-urbanization, primarily characterized by declining agricultural land and a growing population, is a primary driver of peri-urban dynamics. As urban-centric activities and demands rise, unmanaged urban sprawl causes socio-cultural disruptions, pollution, and economic instability. The intricate processes dependable for these negative impacts are primarily associated with population dynamics and land use changes. This study investigates the trends of demographic and land-use changes in the peri-urban area and evaluates the interrelationships between these two factors.  We utilize the multi-decade population and land-use transformations from 1990 to 2020 in the peri-urban area of Denpasar City – one of the most metropolitan areas in Indonesia. The results reveal that the peri-urban areas encountered unprecedented population growth and urban sprawl. The results indicate that the inner peri-urban area has encountered more substantial changes in population and land use than the outer area. Nevertheless, specific demographic trends have a positive influence on peri-urban land-use transformation. This elucidates why land use is progressively diverging from household demographic dynamics, specifically in population growth, population density, and the proportion of males and individuals in non-productive age groups. The interlinked relationship between these variables suggests land use conversion in peri-urban areas. The results emphasize the need for governmental planners to carefully examine demographic and land-use trends when formulating regional cross-border plans to promote sustainable peri-urban development.